ACUTE AND CHRONIC EFFECT OF CYANIADE ON SURVIVAL RATE, BEHAVIOR, AND REPRODUCTION OF DAPHNIA SP. - Pattiwael, Melky R; Mangindaan, Remy E. P; Prabowo, Rudi; Rumengan, Inneke F. M (Graduate Program of Sam Ratulangi University, 2013)
Cyanide (CN) through leaching process in the gold processing could produce tailings that have negative impacts on the aquatic environment. To determine the acute and chronic effects of cyanide on aquatic organisms, toxicity tests have been conducted in the laboratory using Daphnia sp.This zooplankton organism is recommended by APHA as standard test animals. In this study the test concentrations refer to the Ministerial Decree No. 202 of 2004 and Government Regulation No. 82 of 2001. Cyanide was analyzed as free CN and WADS CN. The result of acute toxicity test using cyanide solution showed that Daphnia could survive a maximum concentration of 0.2 ppm. LC50 values for 24 and 72 hours were 0,59 mg/L and 0,10 mg/l, respectively. The LT50 was found at 42 hours. Daphnia sp. produced different numbers of offspring at different CN concentrations, and changed their reproduction pattern from parthenogenesis to sexual reproduction after exposure to a cyanide concentration of 0.1 ppm for 24 hours© Sianida (CN) melalui proses leaching dalam proses pengolahan emas menghasilkan limbah yang dapat memberi dampak negatif bagi lingkungan perairan. Untuk mengetahui sampai seberapa jauh CN dapat memberi efek akut dan kronis terhadap biota air, telah dilakukan uji toksisitas di laboratorium dengan menggunakan Daphnia sp. Zooplankton ini direkomendasikan oleh APHA sebagai salah satu hewan uji standar. Dalam penelitian ini konsentrasi uji yang dipakai mengacu pada peraturan yang berlaku, yaitu Keputusan Menteri No. 202, Tahun 2004, dan Peraturan Pemerintah No. 82, Tahun 2001. Analisis sianida yang dihitung adalah nilai free CN dan WADS CN. Hasil penelitian uji toksisitas akut dengan menggunakan larutan sianida didapati Daphnia mampu bertahan hidup sampai pada konsentrasi 0,2 ppm dan nilai LC50 berada pada konsentarsi 0,1 ppm serta LT50 pada jam ke 42. Hasil uji efek kronis, Daphnia sp. menghasilkan jumlah anakan yang berbeda pada konsentrasi CN yang berlainan, dan mengalami perubahan pola reproduksi dari partenogenesis menjadi seksual setelah dipaparkan pada kosentrasi sianida 0,1 ppm selama 24 jam©